Public attitudes in the United States toward insurance coverage for in vitro fertilization and the provision of infertility services to lower income patients - Jacqueline R. Ho, M.D., M.S; Lusine Aghajanova, M.D., Ph.D; Evelyn Mok-Lin, M.D; Jacquelyn R. Hoffman, M.D; James F. Smith, M.D., M.Sc; Christopher N. Herndon, M.D (Elsevier, 2022)
Objective: To assess attitudes and factors that influence public opinion in the general US population toward insurance coverage and provision of infertility care to lower income patients. Design: Cross-sectional survey. Setting: Online. Patient(s): A nationally representative sample of US residents. Intervention(s): Questionnaire with multiple choice and open response questions. Main Outcome Measure(s): Public attitudes toward in vitro fertilization and infertility care coverage for lower income patients. Result(s): A total of 1,027 (90.2%) participants completed the survey, among whom 620 (60.4%) had private insurance, 275 (26.8%) had Medicare/Medicaid, and 56 (5.5%) were uninsured. The majority (916, 89.2%) did not consider infertility a disease. Over half of the respondents (568, 55.3%) supported private insurance coverage of infertility services, including for in vitro fertilization. Most respondents, 735 (71.6%) believed that the prevalence and psychosocial impact of infertility were equal among the lower and higher income people. The majority of respondents with an opinion (512, 67.6%) believed that doctors should provide infertility treatments regardless of the income level of the patients. Of supporters, 40.1% believed in the right to have a family regardless of income, and 38.2% believed that doctors had a social responsibility to provide infertility services. After adjusting for covariates, age <45 years, noncollege graduates, desiring more children, believing that infertility was a disease, and residence in the Northeast region remained significant predictors for support of private insurance coverage. Conclusion(s): Public perception of infertility as a disease is one of the strongest predictors of support for insurance coverage for infertility services, underscoring the need for enhanced advocacy and education in the general public.